Education, work and vocational training in the MST: the experience of the Course of Agroecology of the Milton Santos School - Erika Porceli Alaniz; Neusa Maria Dal Ri (Universidade Federal do Norte do Tocantins, 2019)
In the process of occupation and conquest of agrarian reform settlements, the Movement of Landless Workers implants innumerable educational experiences at different levels and modalities of education to meet the right to education and the need for political and technical training children and youth. This article presents a reflection on the meaning of education and work in the technical course in Agroecology in a school of MST. We look for attempted to grasp the meaning of work as an educational principle effected by the school, as well as identifying the overlap between the technical and political dimension in the training process. It is empirical research conducted at the School Milton Santos, Paraná, through observation and semi-structured interviews with leaders and students. The findings showed that the students are formed through real work experienced in school and in the settlements as complementary moments, aimed at social struggle.